Functional and Structural Aspects of La Protein Overexpression in Lung Cancer. Issue 24 (4th December 2020) - Kaliatsi, Eleni G.; Argyriou, Aikaterini I.; Bouras, Georgios; Apostolidi, Maria; Konstantinidou, Parthena; Shaukat, Athanasios-Nasir; Spyroulias, Georgios A.; Stathopoulos, Constantinos
Graphical abstract: Highlights: La overexpression leads to increased cell proliferation and motility in A549 cells. La over expression induced induces hypophosporylation of 4E-BPs and IRES-mediated translation. NMR-driven studies revealed that La motif alone has specific RNA binding properties. Abstract: La is an abundant phosphoprotein that protects polymerase III transcripts from 3′-5′ exonucleolytic degradation and facilitates their folding. Consisting of the evolutionary conserved La motif (LAM) and two consecutive RNA Recognition Motifs (RRMs), La was also found to bind additional RNA transcripts or RNA domains like internal ribosome entry site (IRES), through sequence-independent binding modes which are poorly understood. Although it has been reported overexpressed in certain cancer types and depletion of its expression sensitizes cancer cells to certain chemotherapeutic agents, its role in cancer remains essentially uncharacterized. Herein, we study the effects of La overexpression in A549 lung adenocarcinoma cells, which leads to increased cell proliferation and motility. Expression profiling of several transcription and translation factors indicated that La overexpression leads to downregulation of global translation through hypophosphorylation of 4E-BPs and upregulation of IRES-mediated translation. Moreover, analysis of La localization after nutrition deprivation of the transfected cells showed a normal distribution in the nucleus and nucleoli. Although the RNA binding capacity of La has been primarily linked to the synergy between the conserved LAM and RRM1 domains which act as a module, we show that recombinant stand-alone LAM can specifically bind a pre-tRNA ligand, based on binding experiments combined with NMR analysis. We propose that LAM RNA binding properties could support the expanding and diverse RNA ligand repertoire of La, thus promoting its modulatory role, both under normal and pathogenic conditions like cancer.